Vactor ontologies: framing acting within a motion capture context. Issue 3 (2nd September 2022) - Kennedy, Jason
ABSTRACT: While an actor's performance in a stage play may be seen as a continuous and unmediated form of acting, an actor's performance in a film is constructed through shot framing, editing, effects work, and other cinematic apparatuses. With the advent of digital filmmaking, constructed performances have become more complex and nuanced, especially through the use of motion capture (MoCap). This research explores how we frame acting within a motion capture context – and specifically, how this affects our larger understanding of what is acting and how acting can be constructed. What does acting become when the product of acting starts as data and finishes as computer-generated images that preserve the source-actor's 'original' performance to varying degrees? Is the source actor solely responsible for the MoCap performance we see on screen, or should other people within the production pipeline receive credit for their creative contributions to the finished acting result? What is at stake in differentiating film acting in MoCap from profilmic performances? Through consolidating and linking theoretical and practical considerations of screen acting in motion capture, this paper proposes a number of ways to conceive of acting and presence within a virtual acting context.